Are Serious Games an Effective Teaching Tool in Anatomy Education? A Systematic Review - Tariq Al Habsi; Hashim Alibrahim; Adhari Al Zaabi; Sreenivasulu Reddy Mogali; Tan Jun Wen; Mickael Joseph; Eiman Al-Ajmi; Srinivasa Rao Sirasanagandla (Applied Sciences)
Background: Human anatomy is a crucial component of medical curricula, requiring innovative methods to enhance students’ learning outcomes. Recently, various technology-based methods have emerged to address the limitations of traditional anatomy teaching methods. Among these, serious games have emerged as a promising tool demonstrating effectiveness in achieving various learning outcomes. This systematic review aims to evaluate the effectiveness of serious games in anatomy education and identify gaps in literature. Methods: Following PRISMA guidelines, a comprehensive search of databases including PubMed, Scopus, and Google Scholar was performed. Of 900 records identified, 24 records were eligible for the full text review. Of these, 14 studies were included eventually for detailed analysis. Study quality was assessed using the Newcastle–Ottawa Scale. Results: The results showed that the key learning domains assessed were knowledge acquisition, engagement, perception, and skills development. Most studies reported positive outcomes in terms of students’ performance and satisfaction. Despite these findings, variations in study design, sample size, and assessment methods were noted, limiting the generalizability of results. Conclusions: Serious games represent a novel supplement to anatomy education, fostering improved learning outcomes and engagement. However, future work should focus on well-crafted randomized controlled trials to effectively evaluate the impact of using serious games in anatomy teaching with combined qualitative and quantitative evaluation approaches.